Geo-hazard map of cover-collapse sinkholes in the Kinta Valley, Perak Malaysia - Alkouri, Omar; Omar, Husaini (2007)
Sinkholes have a negative effect on urban development, Intense development witin the Kinta Valley, however, has resulted in geo-hazard occurences, Geo-hazards have become a threat to humans in addition to their negative impact on the socio-economic dimension, particularly, in Kinta valley Karst have been deteriorating by dramatic changes occured in past and continues in the future due to close relationship between the fast rate of lateral urbanization expansion and extensive dimensional retreating by surface mining and quarrying activities. Consequently, many environmental problems occured, especially conserning geo-hazards (Sinkholes, rock fall) along with technological advances in Remote Sensing and Geographical Information Systems (GIS). This has given rise to increased efforts by researchers, engineers, and planners to better understand the spatial distribution of karst features that characterize these regions. GIS applications enable researchers to objectively identify the condition that trigger karst hazards and develops spatial database. However, karst formations develop in very specific ways that are influenced by the unique local conditions of the area.